GREEN MAINTENANCE FOR HERITAGE BUILDINGS: LATERITE STONE REPAIR APPRAISAL - Imaduddin Abdul Halim; Brit Anak Kayan; Nurush Syahadah Mahmud (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Maintenance is widely accepted as important mechanism for survival of heritage buildings. Progressively, their maintenance had shift towards sustainability, encompassing economic, societal and environmental domain. Meanwhile, the efficiency of maintenance and repair for heritage buildings is no exception and also conforms to these broad domains. Moreover, previous works and study on their repair appraisal within environmental domain garnered little attention. Emergently, low carbon consideration for heritage buildings became increasingly important in achieving a sustainable repair and this was supported by ‘Green Maintenance’ concept and methodology. Primarily, the aim of this paper is to gives insight on how ‘Green Maintenance’ has capability to evaluate low carbon repair for laterite stone structure, based on selected case studies of Bastion Middleburg and St Paul’s Church of the UNESCO World Heritage Site of Melaka, Malaysia. Notably, it is discovered that laterite stone repair appraisal results based on the model shows that cumulative embodied carbon expenditure expended from repair can be represented in the form of Environmental Maintenance Impact (EMI) of ‘Green Maintenance’ model. Significantly, the EMI of the model also shows its ability to relay the ‘true’ CO2 emissions for laterite stone repair, within selected maintenance time frame. Additionally, calculation procedures through formulaic expression of the model enabled evaluation of EMI for repair within ‘cradle-to-site’ boundary of Life Cycle Assessment (LCA). Most importantly, Green Maintenance model shows its ability as a tool for maintenance decision-making, which enables determination of sustainable repair approach for heritage buildings.